2023
DOI: 10.1021/acs.iecr.2c04614
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoates Production: A Challenge for the Plastic Industry

Fernando Guzmán-Lagunes,
Phavit Wongsirichot,
James Winterburn
et al.

Abstract: The accumulation of petroleum-based plastics in the environment has heightened the necessity of finding alternative materials with similar properties and lower environmental impact. Polyhydroxyalkanoates (PHAs) are a group of naturally occurring polyesters that have been investigated for several decades as potential substitutes for commonly used plastics. PHAs are biodegradable and biocompatible polymers derived from renewable resources. From this point of view, their industrial implementation represents an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 265 publications
0
7
0
Order By: Relevance
“…The natural variability found in these matrices, moreover, represents an additional critical issue for the standardization of the downstream processes aiming at recovering and purifying PHAs. Indeed, it has been reported that changes in the C:N ratios of the substrates led to variations in polymer accumulation, thus requiring a continuous adaptation of the purification protocol [ 9 ]. In particular, the molar mass of the polymer strongly affects its technological properties, thus making the control of the biosynthesis fundamental from the early fermentation stage.…”
Section: Critical Points Related To the Industrial Scale-up Of Pha Pr...mentioning
confidence: 99%
See 4 more Smart Citations
“…The natural variability found in these matrices, moreover, represents an additional critical issue for the standardization of the downstream processes aiming at recovering and purifying PHAs. Indeed, it has been reported that changes in the C:N ratios of the substrates led to variations in polymer accumulation, thus requiring a continuous adaptation of the purification protocol [ 9 ]. In particular, the molar mass of the polymer strongly affects its technological properties, thus making the control of the biosynthesis fundamental from the early fermentation stage.…”
Section: Critical Points Related To the Industrial Scale-up Of Pha Pr...mentioning
confidence: 99%
“…If high-purity PHAs are required, the use of chlorinated solvents or acetone in the extraction and purification stages is required. Enzymatic treatment, chemical treatments with sodium hypochlorite or surfactants, and mechanical disruption are other downstream processing methods that are available [ 9 ]. It must be considered that the purification processes translate into additional demands for energy and chemical substances, which negatively affect the costs and sustainability of bioplastic production.…”
Section: Critical Points Related To the Industrial Scale-up Of Pha Pr...mentioning
confidence: 99%
See 3 more Smart Citations